Myosin VI in the nucleolus of neurosecretory PC12 cells: its involvement in the maintenance of nucleolar structure and ribosome organization - Nowak, Jolanta; Lenartowski, Robert; Kalita, Katarzyna; Lehka, Lilya; Karatsai, Olena; Lenartowska, Marta; Rędowicz, Maria Jolanta (Frontiers in Physiology, 2024)
We have previously shown that unconventional myosin VI (MVI), a unique actin-based motor protein, shuttles between the cytoplasm and nucleus in neurosecretory PC12 cells in a stimulation-dependent manner and interacts with numerous proteins involved in nuclear processes. Among the identified potential MVI partners was nucleolin, a major nucleolar protein implicated in rRNA processing and ribosome assembly. Several other nucleolar proteins such as fibrillarin, UBF (upstream binding factor), and B23 (also termed nucleophosmin) have been shown to interact with MVI. A bioinformatics tool predicted the presence of the nucleolar localization signal (NoLS) within the MVI globular tail domain, and immunostaining confirmed the presence of MVI within the nucleolus. Depletion of MVI, previously shown to impair PC12 cell proliferation and motility, caused disorganization of the nucleolus and rough endoplasmic reticulum (rER). However, lack of MVI does not affect nucleolar transcription. In light of these data, we propose that MVI is important for nucleolar and ribosome maintenance but not for RNA polymerase 1-related transcription.